Antiresonances and Ultrafast Resonances in a Twin Photonic Oscillator - Yannis Kominis; Kent D. Choquette; Anastasios Bountis; Vassilios Kovanis (IEEE Photonics Journal)
We consider the properties of the small-signal modulation response of symmetry-breaking phase-locked states of twin coupled semiconductor lasers. The extended stability and the varying asymmetry of these modes allows for the introduction of a rich set of interesting modulation response features, such as sharp resonances and antiresonances as well as efficient modulation at very high frequencies exceeding the free running relaxation frequencies by orders of magnitude.